2009
DOI: 10.7326/0003-4819-150-3-200902030-00028
|View full text |Cite
|
Sign up to set email alerts
|

Acute Hepatitis E Virus Infection in an HIV-Infected Person in the United States

Abstract: Background Hepatitis E virus (HEV) is an enterically transmitted cause of viral hepatitis rarely noted without international travel. Objective To report the first case of an HIV-infected man with acute hepatitis due to HEV infection who had not traveled outside the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 5 publications
1
22
1
Order By: Relevance
“…Nonetheless, parenteral transmission of HEV has rarely been reported in children, as it seems that this kind of transmission requires more than the regular amounts of blood used in transfusions for children [34]. Nevertheless, other ways of transmission such as person-to-person [31,32,33]and mother-to-child, though seemingly improper, have been suggested by some researchers, too [6,35,36]. Therefore, although the fecal-oral route seems to be the most frequent path of transmission, one cannot ignore the probability of other routes.…”
Section: Epidemiologymentioning
confidence: 99%
“…Nonetheless, parenteral transmission of HEV has rarely been reported in children, as it seems that this kind of transmission requires more than the regular amounts of blood used in transfusions for children [34]. Nevertheless, other ways of transmission such as person-to-person [31,32,33]and mother-to-child, though seemingly improper, have been suggested by some researchers, too [6,35,36]. Therefore, although the fecal-oral route seems to be the most frequent path of transmission, one cannot ignore the probability of other routes.…”
Section: Epidemiologymentioning
confidence: 99%
“…More recent studies focusing on detection of anti-HEV IgM, IgG, or RNA have identified both acute (266,(303)(304)(305)(306)(307)(308)(309)(310)(311)(312)(313) and chronic (266,(268)(269)(270)(271)(272)(273)(274) HEV infections in HIV-positive patients, though it remains unclear whether or not seroprevalence is any greater in people with HIV (272,273,300,309,310,(314)(315)(316)(317)(318). Chronic HEV infections in HIV-positive individuals have been associated with quick progression to cirrhosis (269)(270)(271), though it is not clear whether HEV-linked cryptogenic cirrhosis is more common in HIV-infected individuals than in the general population (310,311,315,319).…”
Section: Immunosuppression and Impaired Viral Clearancementioning
confidence: 99%
“…However, HEV co-infection in patients with HIV is not common and, to date, less than 20 cases have been documented in the literature, and only a handful have had chronic infection, the majority of these cases become cleared of HEV spontaneously. 4,[62][63][64][65][66][67][68][69][70][71][72] In contrast to recipients of a SOT, the key risk factor that determines the development of chronic infection in HIV patients is a low CD4 count. In the five chronic cases described so far, all had CD4 counts <250 mm 3 .…”
Section: Hev Infection In Hiv Patientsmentioning
confidence: 99%